The Holocaust, Israel and 'the Jew'
1 online resource.
Keywords: This book is the first comprehensive study of postwar antisemitism in the Netherlands. It focuses on the way stereotypes are passed on from one decade to the next, as reflected in public debates, the mass media, protests and commemorations, and everyday interactions. The Holocaust, Israel and 'the Jew' explores the ways in which old stories and phrases relating to 'the stereotypical Jew' are recycled and modified for new uses, linking the antisemitism of the early postwar years to its enduring manifestations in today's world., The Dutch case is interesting because of the apparent contrast between the Netherlands' famous tradition of tolerance and the large numbers of Jews who were deported and murdered in the Second World War. The book sheds light on the dark side of this so-called 'Dutch paradox,' in manifestations of aversion and guilt after 1945. In this context, the abusive taunt 'They forgot to gas you' can be seen as the first radical expression of postwar antisemitism as well as an indication of how the Holocaust came to be turned against the Jews. The identification of 'the Jew' with the gas chamber spread from the streets to football stadiums, and from verbal abuse to pamphlet and protest. The slogan 'Hamas, Hamas all the Jews to the gas' indicates that Israel became a second marker of postwar antisemitism. The chapters cover themes including soccer-related antisemitism, Jewish responses, philosemitism, antisemitism in Dutch-Moroccan and Dutch- Turkish communities, contentious acts of remembrance, the neo-Nazi tradition, and the legacy of Theo van Gogh. The book concludes with a lengthy epilogue on 'the Jew' in the politics of the radical right, the attacks in Paris in 2015, and the refugee crisis. The stereotype of 'the Jew' appears to be transferable to other minorities.